Theoretical Review: The Protection of Music Copyrights in the Radio - Wahyu Sasongko (Fiat Justisia: Jurnal Ilmu Hukum, 2019)
Playback of music or songs on the radio has the potential to infringe the copyright songwriters. Based on the applicable legal provisions, namely Law Number 28 the Year 2014 concerning Copyrights, the songwriter is the copyright owner of music which is protected by law.  Therefore, parties who take advantage of music must obtain permission from the copyright owner. Radio companies should get permission from the copyright owner to play the music on their radio station. However, it is difficult to oversee the playback of the music on the radio. In this context, a collective management agency (CMA) emerges, but the presence of a CMA is not mandatory or optional. Therefore, this paper does not involve CMA. In this regard, legal issues arise, namely how to protect music copyrights according to applicable law to attain legal certainty. This paper is a theoretical study of legal theory or legal doctrine relating to the rights of songwriters. In legal science or jurisprudence it is not clearly distinguished between legal doctrine and legal theory. In discussing this issue, firstly it will be discussed about the meaning and types of music copyrights. Next, it will be discussed about the legal construction or legal framework of music copyrights. Based on theoretical studies, songwriters have various rights with specific characteristics so that the treatments must also be accurate. The legal construction of music copyrights is intertwined in a network of legal binding that is influenced by subject and object factors. The subjects involved are interconnected to use the music as its object. The legal relationship between subjects is mutually beneficial or mutual symbiosis. Meanwhile, music as objects is a flexible commodity. Therefore, airing music on the radio is in doubt to be categorized as copyright infringement.